The Influence of Organizational Virtuousness and Psychological Capital on Organizational Citizenship Behavior with Happiness at Work as a Mediator (Study on Bank Employees in the Special Region of Yogyakarta) - Nur Cahyono, Hutdi; Rosita Endang Kusmaryani (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study explores how Organizational Virtuousness and Psychological Capital influence Organizational Citizenship Behavior (OCB) among bank employees in Yogyakarta, with Happiness at Work as a mediating factor. It aims to provide insights into promoting positive employee behavior and well-being amid high-stress banking environments. This study uses a quantitative explanatory approach to explore the causal relationships between Organizational Virtuousness, Psychological Capital, Happiness at Work, and Organizational Citizenship Behavior (OCB) among banking employees in DIY, employing closed-ended questionnaires, Structural Equation Modeling (SEM), and mediation analysis to test the hypotheses. This study concludes that both Organizational Virtuousness and Psychological Capital significantly enhance Happiness at Work, which in turn positively influences Organizational Citizenship Behavior (OCB). Happiness at Work acts as a key mediator, with indirect effects from both Organizational Virtuousness and Psychological Capital on OCB exceeding their direct effects. These findings highlight the importance of fostering optimism, integrity, and resilience to promote employee well-being and prosocial behavior. Organizations are advised to develop supportive cultures and implement targeted programs that build psychological resources and ethical values. Keyword: Bank Employees, Happiness at Work, Organizational Citizenship Behavior (OCB), Organizational Virtuousness, Psychological Capital